Patriotism, Pressure, and Place: Civic Agency in Base Country. Issue 1 (1st January 2019) - Gibbs, Brian
Abstract : This article focuses on how civic agency is taught or not taught by a social studies teacher to the children of soldiers in a largely conservative community and, as a result, how it was learned or not learned. Taken from a larger study investigating individual teacher curricular and pedagogic choice around teaching war near a military base, this article examines the sociopolitical, district-level, student, parent, and community pressures and tensions of teaching war in this context and what impact these pressures have on teaching choice and student sense of civic agency. Findings suggest that the teacher, mostly yielding to the pressure and stress, avoids complexity of perceived dangerous content, which left most students with an unchallenged sense of traditional patriotism and duty.